Approaches for the isolation and long-term expansion of pericytes from human and animal tissues - Alvino, Valeria Vincenza; Mohammed, Khaled Abdelsattar Kassem; Gu, Yue; Madeddu, Paolo (Frontiers in Cardiovascular Medicine, 2023)
Pericytes surround capillaries in every organ of the human body. They are also present around the vasa vasorum, the small blood vessels that supply the walls of larger arteries and veins. The clinical interest in pericytes is rapidly growing, with the recognition of their crucial roles in controlling vascular function and possible therapeutic applications in regenerative medicine. Nonetheless, discrepancies in methods used to define, isolate, and expand pericytes are common and may affect reproducibility. Separating pure pericyte preparations from the continuum of perivascular mesenchymal cells is challenging. Moreover, variations in functional behavior and antigenic phenotype in response to environmental stimuli make it difficult to formulate an unequivocal definition of bona fide pericytes. Very few attempts were made to develop pericytes as a clinical-grade product. Therefore, this review is devoted to appraising current methodologies’ pros and cons and proposing standardization and harmonization improvements. We highlight the importance of developing upgraded protocols to create therapeutic pericyte products according to the regulatory guidelines for clinical manufacturing. Finally, we describe how integrating RNA-seq techniques with single-cell spatial analysis, and functional assays may help realize the full potential of pericytes in health, disease, and tissue repair.